Pemahaman Pelaku Usaha terhadap Sertifikasi Halal : Studi Kasus Rumah Makan Padang Takana Medan - Zainarti Zainarti; Angger Gumilang Sugiarto; Al Ramzy (Global Leadership Organizational Research in Management, 2025)
Halal certification is a strategic element in ensuring the quality of food products and building the trust of Muslim consumers. This study aims to examine the level of understanding of business actors regarding halal certification through a case study at the Padang Takana Restaurant in Medan City. Using a qualitative approach through observation and in-depth interviews, the results of the study indicate that there are still many MSME actors who do not fully understand the importance of halal certification, both in terms of law and its economic value. The obstacles faced include limited information, low digital literacy, and administrative procedures that are considered complicated. This study emphasizes the importance of government intervention in the form of education and assistance so that business actors can more easily access the halal certification process efficiently and affordably.